Henry Plummer : a novel - Linderman, Frank Bird, 1869-1938 (University of Nebraska Press, 2000)
"Sheriff and outlaw Henry Plummer needed no introduction to the citizens of Montana Territory in the mid-nineteenth century. And well into the twentieth century, Frank Bird Linderman sought out the stories of the people who knew Plummer and ultimately hanged him."--Page 4 of cover